Evaluating the Accuracy, Quality, and Readability of Online Breast Cancer Information - Elsie A. Valencia, BS; Chandler S. Cortina, MD, MS, FSSO, FACS; Adrienne N. Cobb, MD, MS; Lubna N. Chaudhary, MD, MS; Tracy Kelly, MD; Amanda L. Kong, MD, MS, FSSO, FACS (Annals of Surgery Open)
Objective:. To assess the accuracy, quality, and readability of patient-focused breast cancer websites using expert evaluation and validated tools. Background:. Ensuring access to accurate, high-quality, and readable online health information supports informed decision-making and health equity but has not been recently evaluated. Methods:. A qualitative analysis on 50 websites was conducted; the first 10 eligible websites for the following search terms were included: “breast cancer,” “breast surgery,” “breast reconstructive surgery,” “breast chemotherapy,” and “breast radiation therapy.” Websites were required to be in English and not intended for healthcare professionals. Accuracy was evaluated by 5 breast cancer specialists. Quality was evaluated through the DISCERN questionnaire. Readability was measured using 9 standardized tests. Mean readability was compared with the American Medical Association and National Institutes of Health 6th grade recommendation. Results:. Nonprofit hospital websites had the highest accuracy (mean = 4.06, SD = 0.42); however, no statistical differences were observed in accuracy by website affiliation (P = 0.08). The overall mean quality score was 50.8 (“fair”/“good” quality) with no significant differences among website affiliations (P = 0.10). Mean readability was at the 10th grade reading level, the lowest being for commercial websites with a mean 9th grade reading level (SD = 2.38). All websites exceeded the American Medical Association- and National Institutes of Health-recommended reading level by 4.4 levels (P < 0.001). Websites with higher accuracy tended to have lower readability levels, whereas those with lower accuracy had higher readability levels. Conclusion:. As breast cancer treatment has become increasingly complex, improving online quality and readability while maintaining high accuracy is essential to promote health equity and empower patients to make informed decisions about their care.